2012
DOI: 10.1007/s11033-012-2476-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression and tissue localization of renalase, a novel soluble FAD-dependent protein, in reproductive/steroidogenic systems

Abstract: Renalase was initially identified in human kidney as a soluble monoamine oxidase. Here we show that renalase is predominantly expressed in reproductive/steroidogenic systems, with particularly substantial expression in oocytes, granulosa, interstitial and luteal cells of ovary, spermatogenic cells of testis, and cortex of adrenal gland, suggesting its function(s) in maturation of germ cells and steroid hormone regulation. Renalase expression increases in testes and ovaries as mice develop and its expression is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 41 publications
0
18
0
Order By: Relevance
“…Renalase isoform 1 was originally reported to be predominantly expressed in the proximal tubes and glomerulus of the kidney, but was said to be detectable in cardiac muscle, liver tissue and skeletal muscle [11] and the bias for higher expression in the kidney was later confirmed [53]. However, it has since been shown that isoform 1 transcripts are detectable in nerves, adrenal glands, adipose tissue [51], and that expression is prominent in reproductive tissues [54]. Moreover, the Proteomics DB database reports widespread tissue distribution of renalase isoforms 1 and 2 [55].…”
Section: Tissue Distributionmentioning
confidence: 99%
“…Renalase isoform 1 was originally reported to be predominantly expressed in the proximal tubes and glomerulus of the kidney, but was said to be detectable in cardiac muscle, liver tissue and skeletal muscle [11] and the bias for higher expression in the kidney was later confirmed [53]. However, it has since been shown that isoform 1 transcripts are detectable in nerves, adrenal glands, adipose tissue [51], and that expression is prominent in reproductive tissues [54]. Moreover, the Proteomics DB database reports widespread tissue distribution of renalase isoforms 1 and 2 [55].…”
Section: Tissue Distributionmentioning
confidence: 99%
“…Genes expressed selectively or specifically in a certain organ may play crucial physiological and/or functional roles in this particular tissue. Our previous study showed that renalase is predominantly expressed in mice steroidogenic/reproductive systems, including in the ovaries, testes, and adrenal glands, 26 and it is also expressed in mice livers. 27 Although these organs are also involved in cholesterol synthesis and/or metabolism, it is an interesting question whether renalase may be involved in lipid metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…A notable reduction in renalase level in preeclamptic women was observed in the present study when compared to the healthy pregnancies. Previously, it was shown that the manipulation of gonadotropinreleasing hormone (GnRH) might alter the expression of renalase and GnRH antagonists downregulate the renalase secretion [25]. As the placenta has a central role in PE [26], ischemic changes observed during PE possibly accompany low GnRH level and diminish GnRH would facilitate a low level of renalase in pre-eclamptic women.…”
Section: Discussionmentioning
confidence: 99%